Brain pathology in myotonic dystrophy: when tauopathy meets spliceopathy and RNAopathy - Caillet-Boudin, Marie-Laure; Fernandez-Gomez, Francisco J.; Tran-Ladam, Helen; dhaenens, claire-marie; Buee, Luc; Sergeant, Nicolas (Frontiers in Molecular Neuroscience, 2014)
Myotonic dystrophy (DM) of type 1 and 2 (DM1 and DM2) are inherited autosomal dominant diseases caused by dynamic and unstable expanded microsatellite sequences (CTG and CCTG, respectively) in the non-coding regions of the genes DMPK and ZNF9, respectively. These mutations result in the intranuclear accumulation of mutated transcripts and the mis-splicing of numerous transcripts. This so-called RNA gain of toxic function is the main feature of an emerging group of pathologies known as RNAopathies. Interestingly, in addition to these RNA inclusions, called foci, the presence of neurofibrillary tangles (NFT) in patient brains also distinguishes DM as a tauopathy. Tauopathies are a group of nearly 30 neurodegenerative diseases that are characterized by intraneuronal protein aggregates of the microtubule-associated protein Tau (MAPT) in patient brains. Furthermore, a number of neurodegenerative diseases involve the dysregulation of splicing regulator factors and have been characterized as spliceopathies. Thus, myotonic dystrophies are pathologies resulting from the interplay among RNAopathy, spliceopathy, and tauopathy. This review will describe how these processes contribute to neurodegeneration. We will first focus on the tauopathy associated with DM1, including clinical symptoms, brain histology, and molecular mechanisms. We will also discuss the features of DM1 that are shared by other tauopathies and, consequently, might participate in the development of a tauopathy. Moreover, we discuss the determinants common to both RNAopathies and spliceopathies that could interfere with tau-related neurodegeneration.